Insight into the city/town names of Latvia - Laimude Balode (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2017)
Abstract. The origin of place names is a research topic for linguists (or onomasticians) and geographers, but since ancient times a wide range of people have also been interested in the subject. As Latvia is the closest neighbour to both Lithuania and Estonia, they share, to a large extent, a common history, as well as – because of this fact – a number of borrowed common words and names. This article is based on the toponymical material included in the short dictionary of Latvian geographical names entitled “No Abavas līdz Zilupei” (“From Abava to Zilupe. The origin of Latvian geographical names”), which was compiled by Laimute Balode and Ojārs Bušs and published in Rīga in 2015. It offers insights into the contemporary situation of Latvian oikonyms as well as providing comparisons of the names of inhabited places with their historical names.